Жүктілікті жасанды түрде үзудің алдын алудағы діни уағыздарды деректанулық тұрғыдан талдау (ҚазҰУ Хабаршысы. Дінтану сериясы, 2022)
The article discusses the religious and ethical problem – the artificial termination of pregnancy, more precisely – the fight against abortion by explaining and interpreting religious texts (the verses of the suras of the Koran and the hadiths of the Prophet Muhammad (Peace be upon him) concerning the prohibition. For writing this article, the verses of the suras and hadiths have been collected, directly and indirectly concerning the prohibition or prevention of abortion. The analysis of religious texts is especially important for the prevention of abortion, such a problematic issue of all times, including modernity, for any category of women of reproductive age.